CREATIVE COMPETENCE IS IMPORTANT VECTOR OF PREPARING FUTURE TEACHER - L. N. Egamberdieva (Galaxy International Interdisciplinary Research Journal, 2022)
The article is devoted to the development of creative competence of students in the process of independent work. The directions of the formation of the pedagogical competence of the individual in the university are named.